Comparing the effect of two educational interventions on mothers' awareness, attitude, and self-efficacy regarding sexual health care of educable intellectually disabled adolescent girls: a cluster randomized control trial - Shadi Goli; Mahnaz Noroozi; Mehrdad Salehi (BMC, 2021)
Abstract Background Sexual problems of intellectually disabled adolescents are associated with their inability to understand sexuality. Given the important role of parents in forming the attitude of their adolescents towards sexuality, the present study aimed to compare the effect of two educational interventions on mothers' awareness, attitude and self-efficacy regarding sexual health care of intellectually disabled adolescent girls. Materials and methods This cluster randomized control trial was conducted in six intellectually disabled adolescent education centers in Isfahan, Iran in 2018. The centers were randomly assigned to intervention groups (group training and training through booklet) and control group. Mothers of educable intellectually disabled adolescent girls (n = 81) were entered into the three groups using convenience sampling and their awareness, attitude and self-efficacy regarding sexual health care of adolescent girls were assessed using questionnaires before and after the educational intervention. Data were analyzed using descriptive and inferential statistical methods. Results The mean score of mothers' awareness, attitude and self-efficacy in each of the "group training", "training through booklet group" and "control group" was significantly different after the intervention compared to before the intervention (p < 0.05). The mean score of mothers' awareness and self-efficacy after the intervention in the "group training" was higher than the "control group" and "training through booklet group" (p < 0.001). The mean score of mothers' awareness and self-efficacy after the intervention in the "training through booklet group" was higher than in "control group" (p = 0.005, p = 0.02). Also, after the intervention, the mean score of mothers' attitude in the "group training" was higher than the "control group" and the "training through booklet group" (p < 0.001), but there was no significant statistical difference between the mean score of mothers' attitude in "control group" and "training through booklet group" (p > 0.05). Conclusion Implementation of the group training intervention for mothers of intellectually disabled adolescent girls in comparison with training through booklet was associated with a greater increase in their awareness, attitude and self-efficacy regarding sexual health care of adolescent girls. Therefore, group training is suggested as a suitable way to educate mothers about sexual health care of intellectually disabled adolescent girls. Trial registration IRCT, IRCT20160224026756N5. Registered 22 June 2018, https://en.irct.ir/user/trial/31704/view .